Syrian refugees arriving in Germany: choice of corridor and individual characteristics of forced migrants - Pries, Ludger; Zulfikar Savci, Berna Safak (Frontiers in Sociology, 2023)
In 2015 and 2016, almost two and a half-million forced migrants entered the European Union. Most of them arrived in European Union from Syria, but there are also forced migrants from Iraq, Afghanistan, and other countries. While many of them used the so-called Balkan route after passing through Turkey, others arrived via Lebanon or Turkey to Greece, or some of them went through North African countries, mainly Egypt and Libya. Why did refugees use such different migration corridors? Is it a matter of economic resources, of education and knowledge or of family ties and social networks? In this paper, we analyze the migration corridors of those Syrian refugees who arrived in Germany between 2014 and 2016. We use a unique data set of 3.125 refugees and identify the main migration corridors of Syrian forced migrants and analyze the socio-demographic and journey-related context factors of these routes. Using different routes of refuge correlates with person-related variables and with journey-related context factors.